Upaya Gerakan My Stealthy Freedom dalam Menyuarakan Kesetaraan Gender Pada Perempuan Iran Pada Tahun 2014 – 2019 - Putri, Kadek Dwi Sanjani; Kumala Dewi, Putu Ratih; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
Iran is one of the countries that has problems with gender equality, ranking 141 out of 145 countries regarding gender equality in 2015. After the 1979 Islamic Revolution, Iran did experience a setback in terms of gender equality caused by many changes in state regulations and laws that severely limit women's rights and tend to discriminate. This study aims to analyze various protests and resistance efforts by Iranian women to achieve gender equality in Iran, such as forming Zanan Magazine, forming social movements such as One Million Signature and The Stop Stoning Forever. The analytical method used in this study is qualitative descriptive research, data collection technique is literature study by taking sources from reputable journals. The results of this study indicate that another social movement that has also emerged as a result is My Stealthy Freedom which was born in 2014 and started as a social movement through social media. My Stealthy Freedom seeks to voice gender equality with various methods